Elevated carbon dioxide reduces emission of herbivore‐induced volatiles in Zea mays. (23rd June 2017) - Block, Anna; Vaughan, Martha M.; Christensen, Shawn A.; Alborn, Hans T.; Tumlinson, James H.
Abstract: Terpene volatiles produced by sweet corn ( Zea mays ) upon infestation with pests such as beet armyworm ( Spodoptera exigua ) function as part of an indirect defence mechanism by attracting parasitoid wasps; yet little is known about the impact of climate change on this form of plant defence. To investigate how a central component of climate change affects indirect defence, we measured herbivore‐induced volatile emissions in plants grown under elevated carbon dioxide (CO2 ). We found that S. exigua infested or elicitor‐treated Z. mays grown at elevated CO2 had decreased emission of its major sesquiterpene, ( E )‐β‐caryophyllene and two homoterpenes, (3 E )‐4, 8‐dimethyl‐1, 3, 7‐nonatriene and (3 E, 7 E )‐4, 8, 12‐trimethyl‐1, 3, 7, 11‐tridecatetraene. In contrast, inside the leaves, elicitor‐induced ( E )‐β‐caryophyllene hyper‐accumulated at elevated CO2, while levels of homoterpenes were unaffected. Furthermore, gene expression analysis revealed that the induction of terpene synthase genes following treatment was lower in plants grown at elevated CO2 . Our data indicate that elevated CO2 leads both to a repression of volatile synthesis at the transcriptional level and to limitation of volatile release through effects of CO2 on stomatal conductance. These findings suggest that elevated CO2 may alter the ability of Z. mays to utilize volatile terpenes to mediate indirect defenses. Abstract : Herbivore‐induced volatiles produced by Zea mays attract parasitoid wasps as part of an indirect defence mechanism against insect pests; yet little is known about the impact of atmospheric changes such as elevated carbon dioxide on this form of plant defence. In this study, we found that elevated carbon dioxide reduced the emission of herbivore‐induced sesquiterpene and homoterpene volatiles from Z. mays . This reduction is likely due to repressed transcription of volatile synthesis genes and limitation of volatile release through reduced stomatal conductance. These data indicate that elevated carbon dioxide might reduce the effectiveness of this form of indirect defence in Z. mays .